Syncope, Hypotension, and Falls in the Treatment of Hypertension: Results from the Randomized Clinical Systolic Blood Pressure Intervention Trial. Issue 4 (30th March 2018) - Sink, Kaycee M.; Evans, Gregory W.; Shorr, Ronald I.; Bates, Jeffrey T.; Berlowitz, Dan; Conroy, Molly B.; Felton, Deborah M.; Gure, Tanya; Johnson, Karen C.; Kitzman, Dalane; Lyles, Mary F.; Servilla, Karen; et al.
Abstract : Objective: To determine predictors of serious adverse events (SAEs) involving syncope, hypotension, and falls, with particular attention to age, in the Systolic Blood Pressure Intervention Trial. Design: Randomized clinical trial. Setting: Academic and private practices across the United States (N = 102). Participants: Adults aged 50 and older with a systolic blood pressure (SBP) of 130 to 180 mmHg at high risk of cardiovascular disease events, but without diabetes, history of stroke, symptomatic heart failure or ejection fraction less than 35%, dementia, or standing SBP less than 110 mmHg (N = 9, 361). Intervention: Treatment of SBP to a goal of less than 120 mmHg or 140 mmHg. Measurements: Outcomes were SAEs involving syncope, hypotension, and falls. Predictors were treatment assignment, demographic characteristics, comorbidities, baseline measurements, and baseline use of cardiovascular medications. Results: One hundred seventy‐two (1.8%) participants had SAEs involving syncope, 155 (1.6%) hypotension, and 203 (2.2%) falls. Randomization to intensive SBP control was associated with greater risk of an SAE involving hypotension (hazard ratio (HR) = 1.67, 95% confidence interval (CI) = 1.21–2.32, P = .002), and possibly syncope (HR = 1.32, 95% CI = 0.98–1.79, P = .07), but not falls (HR = 0.98, 95% CI = 0.75–1.29, P = .90). Risk of all three outcomes was higher for participants with chronic kidney disease or frailty. Older age was also associated with greater risk of syncope, hypotension, and falls, but there was no age‐by‐treatment interaction for any of the SAE outcomes. Conclusions: Participants randomized to intensive SBP control had greater risk of hypotension and possibly syncope, but not falls. The greater risk of developing these events associated with intensive treatment did not vary according to age. Abstract : See related editorial byMichael W. Rich .